Effect of plyometric versus complex training on core strength, lower limb, and upper limb power in male cricketers: a randomized controlled trial - Ali, K.; Gupta, S.; Hussain, M. E.; Alzhrani, M.; Manzar, M. D.; Khan, M.; Alghadir, A. H. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Complex training is found effective in improving physical performance in various sports. There is a paucity of research evidence comparing the efficacy of complex vs. plyometric training in cricket players. The study aimed to compare the efficacy of complex and plyometric training on physical performance parameters in cricket players.